2013
DOI: 10.1074/jbc.m113.450023
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mechanistic Insights into LEOPARD Syndrome-Associated SHP2 Mutations

Abstract: Background:The mechanism by which SHP2 mutations cause LEOPARD syndrome is poorly understood. Results: LEOPARD syndrome mutations impair SHP2 activity but increase its propensity for an open and active conformation. Conclusion: LEOPARD syndrome SHP2 mutants bind preferentially to upstream activators to prolong substrate turnover, thus engendering gain-of-function phenotypes. Significance: The study provides a framework for understanding how individual SHP2 mutations cause diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
187
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(201 citation statements)
references
References 48 publications
13
187
0
1
Order By: Relevance
“…Crystal structure analysis and computational modeling have provided mechanistic insights regarding the consequences of SHP2 mutations (18,19). Normally, SHP2 phosphatase activity is regulated by an intramolecular conformational switch that oscillates between a closed and open conformation upon binding to phosphotyrosyl-containing proteins.…”
Section: Y279c/y279cmentioning
confidence: 99%
“…Crystal structure analysis and computational modeling have provided mechanistic insights regarding the consequences of SHP2 mutations (18,19). Normally, SHP2 phosphatase activity is regulated by an intramolecular conformational switch that oscillates between a closed and open conformation upon binding to phosphotyrosyl-containing proteins.…”
Section: Y279c/y279cmentioning
confidence: 99%
“…NS mutations predominantly reside in the interface between the N-SH2 domain and the PTP domain, resulting in the disruption of the closed conformation and enhanced catalytic activity of NS-Shp2 (Keilhack et al, 2005;Nakamura et al, 2009). By contrast, most LS mutations reside close to the active site and result in strongly reduced, yet detectable, catalytic activity (Keilhack et al, 2005;Hanna et al, 2006;Yu et al, 2013). How two mutations with opposite effects on catalytic activity result in syndromes withsimilar clinical symptoms is a conundrum that still needs to be resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Our patient demonstrated the rare manifestation of concurrent JMML and HCM. Recent research demonstrated that catalytically impaired LS‐associated SHP2 mutants could display gain‐of‐function properties because of their ability to localize to the vicinity of substrates for longer periods of time, thereby affording the opportunity for prolonged substrate turnover and sustained RAS/ERK1/2 activation 37, 38. These observations may account for this apparent contradiction of having both HCM and JMML due to p.Thr42Ala mutation in PTPN11 .…”
Section: Discussionmentioning
confidence: 99%